Recurrent pulmonary embolism in an asthmatic patient who had interrupted inferior vena cava with azygous continuation - Aylin Okur; Yavuz Selim Intepe; Halil Ibrahim Serin; Uğur Yıldırım; Ertuğrul Mavili (KARE Publishing, 2014)
A 45-year-old woman with a history of recurrent pulmonary embolism was admitted to the emergency clinic with dyspnea, wheezing and tachypnea. Partial deep vein thrombosis of the popliteal vein was seen on Doppler sonography. On the contrast-enhanced thorax computed tomography (CT) scan, a clot was detected in the right main pulmonary artery and its major descending branch. Moreover, the azygos vein was prominently dilated. Abdominal multi-slice computed tomography (MSCT) scan revealed absence of the hepatic segment of the inferior vena cava (IVC) with continuation of the IVC as a dilated right-sided azygos vein. The hepatic veins were draining directly into the right atrium. Thus, we discuss herein this rare anatomic variant presented with recurrent pulmonary embolism, together with the findings on MSCT.